The municipal theatre of Trujillo: The decline and rebirth of a historical monument in Peru - Aguado Peña, Sergio Enrique (2022)
The municipal theater of Trujillo is considered a historical monument of Peru under the R.S. N° 290072-ED, since December 28, 1972. The present investigation analyzes the monument from its beginnings at the end of the 19th century to the present. The article describes the physical space of the theater, as well as the cultural life that was generated in this important cultural site. Within the historical development, it analyzes its beginnings until its destruction in 1910 after a voracious fire that completely destroyed the structure of the theater. The study has considered its subsequent reopening as part of the celebrations of the centenary of Peru's independence until its present day.